Gout and its impact on physical activity - Joanna Wojtania; Kacper Płeska; Michał Łepik; Zofia Uszok; Krzysztof Rosiak; Kacper Reguła; Kamil Waloch; Szymon Piaszczyński; Andrzej Czajka; Bartłomiej Szymański (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Gout is the most common rheumatic disease in adults, with prevalence ranging from 0.1% to about 10%. It results from the accumulation of monosodium urate crystals (MUC) in the joints and tissues. A thorough understanding of the clinical presentation, diagnostic factors and available treatment options can significantly reduce the prevalence of gout attacks, minimize joint damage and improve patients' physical function. The aim of this article is to provide clinicians and patients with a summary of the most recent information regarding this condition in order to decrease risk of joint damage and ultimately enhance patient's quality of life. Review methods: A review of the literature from PubMed (2010-2023) was conducted. The articles were selected based on specific keywords and then evaluated for their significance and suitability for inclusion in this review. Description the state of knowledge: Gout is an inflammatory arthritis associated with hyperuricemia, defined as elevated level of uric acid in the blood (> 7 mg/dl (420 µmol/l)). Initially, acute gouty arthritis is characterised by sudden onset of severe pain, erythema and swelling, significantly reducing range of movement. However, as disease progresses, chronic, tophaceous gout can develop potentially leading to bone deformities and other complications. Treatment of gout includes management of the attacks and chronic uric acid-lowering therapy. Summary: Gout is a complex disease with various factors contributing to its clinical presentation. Its management requires a multidisciplinary approach including medication management, dietary counselling and lifestyle modification. Early diagnosis as well as appropriate treatment are essential to optimise patient outcomes and maintain patients' physical function.